Influence of Alkaline/Hydrogen Peroxide Treatment on the Properties of Different Natural Cellulosic Fibers - Koschevic, Marivane Turim; dos Santos, Maycon; dos Santos Garcia, Vitor Augusto [UNESP]; Fakhouri, Farayde Matta; Velasco, José Ignácio; de Arruda, Eduardo José; Martines, Marco Antonio Utrera; da Silveira, Tayla Fernanda Serantoni; Bittencourt, Paulo Rodrigo Stivall; Dufresne, Alain; Martelli, Silvia Maria (Springer Nature, 2024)
This study, which has been addressed to the treatment of natural cellulosic fibers, aimed to investigate some properties of cattail, babassu coconut husk, Barú coconut husk, Brazil Nutshell husk, soybean pod, and peanut pod fibers, with alkaline/hydrogen peroxide. The fibers before and after the treatment were characterized by determination of the cellulose and lignin content as determined by scanning electron microscopy, color parameters, FTIR, X-ray diffraction, and thermal properties. As a result, the treatment has been effective in the partial removal of amorphous non-cellulosic polysaccharides, consequently increasing the availability of crystalline cellulose. The FTIR showed a reduction of the bands referring to lignin, the XRD indicated an increase in the crystallinity index, and the SEM analysis showed that the surface of the treated fibers became less rough and more homogeneous when compared with untreated fibers and that the thermal stability of the treated fibers had increased.
Keywords: Cellulose; Natural fibers; Physicochemical modifications; Sustainable materials